The Role and Function of the Ontario Ombudsman - Sirskyj, Borys (My University, 1978)
The purpose of this thesis will be to examine and evaluate the office of the Ombudsman in the province of Ontario since it was created in May, 1975. We suggest that this is a unique mechanism of administrative control over bureaucracy. The significance of the Ombudsman's office is twofold. First the Ombudsman bridges the gap between government and the people by providing the citizens of Ontario with an office where they can lodge their complaints against unfair administrative decisions and through which they can get their grievance redressed.
Secondly, the Ombudsman's office promotes the general efficiency of administration whereby the Ombudsman's recommendations and admonitions correct administrative -malpractices and prevent their recurrence by acting as a set of guidelines for government officials. In this manner, through the improvement of government administration and thereby preventing the recurrence of administrative injustice, the Ombudsman provides both direct and indirect protection a gainst unfoun ded and unjust administrative decisions.
Hence, as the range of such democratic institutions widens, the need for an understanding of its aims and principles becomes more pressing. It is with the hope of making some contribution to the understanding of the Ombudsman's office, particularly in the province of Ontario, that this thesis is being written.
Keywords: Political Science; Political Science